Incubation Temperature and Lighting: Effect on Embryonic Development, Post-Hatch Growth, and Adaptive Response - YALCIN, Servet; Özkan, Sezen; Shah, Tahir (Frontiers in Physiology, 2022)
During incubation, the content of the egg is converted into a chick. This process is controlled by incubation conditions, which must meet the requirements of the chick embryo to obtain the best chick quality and maximum hatchability. Incubation temperature and light are the two main factors influencing embryo development and post-hatch performance. Because chicken embryos are poikilothermic, embryo metabolic development relies on the incubation temperature, which influences the use of egg nutrients and embryo development. Incubation temperature ranging between 37 and 38°C (typically 37.5–37.8°C) optimizes hatchability. However, the temperature inside the egg called “embryo temperature” is not equal to the incubator air temperature. Moreover, embryo temperature is not constant, depending on the balance between embryonic heat production and heat transfer between the eggshell and its environment. Recently, many studies have been conducted on eggshell and/or incubation temperature to meet the needs of the embryo and to understand the embryonic requirements. Numerous studies have also demonstrated that cyclic increases in incubation temperature during the critical period of incubation could induce adaptive responses and increase the thermotolerance of chickens without affecting hatchability. Although the commercial incubation procedure does not have a constant lighting component, light during incubation can modify embryo development, physiology, and post-hatch behavior indicated by lowering stress responses and fearful behavior and improving spatial abilities and cognitive functions of chicken. Light-induced changes may be attributed to hemispheric lateralization and the entrainment of circadian rhythms in the embryo before the hatching. There is also evidence that light affects embryonic melatonin rhythms associated with body temperature regulation. The authors’ preliminary findings suggest that combining light and cyclic higher eggshell temperatures during incubation increases pineal aralkylamine N-acetyltransferase, which is a rate-limiting enzyme for melatonin hormone production. Therefore, combining light and thermal manipulation during the incubation could be a new approach to improve the resistance of broilers to heat stress. This review aims to provide an overview of studies investigating temperature and light manipulations to improve embryonic development, post-hatch growth, and adaptive stress response in chickens.